Effect of polymeric debris on the tribological behavior of diamond-like carbon films - Eun, KY; Lee, KR; Yoon, ES; Kong, HS (ELSEVIER SCIENCE SA LAUSANNE, 1996)
Tribological behaviors between diamond-like carbon (DLC) films and steel ball (AISI 52100) were investigated under a vacuum (4x10(-3) Pa) and ambient air with controlled relative humidity. The DLC films were prepared on Si wafer by r.f. plasma assisted chemical vapor deposition using benzene (C6H6) at a pressure of 1.33 Pa. In the present work, we focused on the friction behavior with increasing number of passes. In high vacuum, the coefficient of friction under the normal load of 4.9 N, decreases from 0.15 to a minimum value of 0.04 at about 200 passes. For higher number of passes, however, the coefficient fluctuated in the range from 0.1 to 0.3. This instability of friction was not observed under higher loads in high vacuum. The present work showed that the oxidation of the DLC surface occurs during the tribe-test even in high vacuum, which results in the formation of polymeric roll-shaped debris. The instability in friction was related to the formation of the polymeric debris. In humid air, the coefficient of friction was measured between 0.15 and 0.2. Fluctuated behavior of friction, however, was not observed in humid air.
Keywords: CHEMICAL VAPOR-DEPOSITION; AMORPHOUS-CARBON; THIN-FILMS; WEAR; FRICTION; SILICON; LAYERS; VACUUM